Peningkatan Kinerja Pengembangan Produk Berkelanjutan Berbasis Budaya Organisasi Lingkungan Dan Kapasitas Daya Serap Keberlanjutan - Hendrajaya Hendrajaya; Samtono Samtono; Bambang Guritno; Haniek Listyorini; Henry Yuliamir; Sukrisno Sukrisno (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to build a conceptual model that seeks to improve the performance of green product development proposed. In this study, the improvement of green product development performance based on environmental organizational culture and green absorption capacity. A construction study methodology was adopted using 200 samples taken from various elements of employees in the manufacturing industry in Central Java and data collected through questionnaires, to test the models and hypotheses in this study, using the author Amos 25 as a tool. data analysis. The results of this study indicate that there is a strategic path to improve product development performance and the second strategy is from organizational culture. green product development. Limitations: This study has limitations, including not being able to define specifically the organizational culture environment. In addition, the sample used is only limited to organizations engaged in the manufacturing industry in the province of Central Java. The results of this study are expected to have a contribution to the development of organizational culture theory and stakeholder theory.